STRUKTUR KEPEMILIKAN KELUARGA DAN KINERJA PERUSAHAAN PADA SEKTOR INDUSTRI DASAR DAN KIMIA - Anna Dewi Debora Silitonga (Business Accounting Review, 2017)
Family firms still dominate in Indonesia, where family firms have disadvantages and advantages that affect company performance. Previous research on the influence of family firms was also inconsistent. This study aimed  to know the affect of family ownership structure on company performance. Were  company performance measured by using ROA. The control variables used were good corporate governance, intensity of competition, company size. The sample used in this research was the companies of basic and chemical industry sector that meet certain criteria and analyzed by using multiple linear regression. The result of this research showed that family ownership structure and good corporate governance had no significant effect to firm performance. Firm size had positive significant effect to firm performance. The intensity of competition variable had negative effect to firm performance.